Administrative Factors and Organization Climate Affecting the Performance of Health Personnel at the Emergency Department in Community Hospital - Padcharin Phomdonko; Prachak Bouphan; NuttapolYotha; Surachai Phimha (Institute of Medico-legal Publications Pvt Ltd, 2021)
This is a cross-sectional analytical study aimed to identify administrative factors and organizational climateaffecting the performance of health personnel at the emergency department in community hospital Roi-Etprovince, Thailand. The study samples selected randomly from Emergency Department were 137 healthpersonnel. Stratified random sampling technique was applied to recruit the respondents from the total of 229health personnel. Similarly, 12 key informants were selected for the qualitative study. In-Depth interviewguidelines was applied to conduct qualitative study. The content validity of the questionnaire was evaluatedby three experts yielding an IOC value more than 0.50 in all questions. The Cronbach’s alpha coefficient ofthe questionnaire was 0.98. Data were collected between 23rd December 2020 to 12th January 2021. Dataanalysis was performed by descriptive statistics and inferential statistics at a significant level at 0.05.The study results showed that the administrative factors such as money, organizational climate suchas dimension of warmth, a dimension of responsibility and dimension of identity were affecting theperformance of health personnel (49.6 % (R2=0.496, p-value<0.001).In conclusion, four factors are affectingthe performance of health personnel. Hence those factors should be addressed, and administration shouldcreate the climate which can address the budget, working objective and goal for the development of theorganization.